ROLE OF EDUCATION in WOMEN EMPOWERMENT - Tripathy, Dr. P. (IJRDO - Journal of Social Science and Humanities Research, 2018)
Education is the key factor for women empowerment, prosperity, development and welfare. Discrimination of women from womb to tomb is well known. There is continued inequality and vulnerability of women in all sectors and women oppressed in all spheres of life, they need to be empowered in all walk of life. In order to fight against the socially constructed gender biases, women have to swim against the system that requires more strength. Such strength comes from the process of empowerment and empowerment will come from the education. And rural development will come from women empowerment. The study is based purely on secondary sources. The study reveals that women of India are relatively disempowered and they enjoy somewhat lower status than that of men in spite of many efforts undertaken by Government. It is found that acceptance of unequal gender norms by women are still prevailing in the society. The study concludes by an observation that access to Education, Employment and Change in Social Structure are only the enabling factors to Women Empowerment.